IMPROVEMENT OF INFORMATION BASE OF MANAGEMENT ACCOUNTING AT THE ENTERPRISES OF THE RADIO-ELECTRONIC INDUSTRY - E. A. Bunto; O. S. Dyakonova (Вестник университета)
The article is devoted to the problems of improving the information base of management accounting at the enterprises of the radio-electronic industry. It has been proved that the effective functioning of organizations of the radio-electronic industry is one of the sources of achieving sustainable socio-economic development of the country, and rational management is based on information resources, which are formed through the movement, processing and structuring of data necessary to improve the efficiency of the enterprise. Qualitative characteristics of management information has been given. The model of accounting and analytical system at the enterprises of the radio-electronic industry, based on the information base available to various users, from the position of the complex nature of theoretical, methodological and organizational issues, has been proposed. The most significant advantages of using the proposed model in the field of management accounting have been highlighted.